Analysing persuasion strategies in online advertising for third-hand cars in Tanzania: translanguaging in the virtual linguistic landscape - Eliniongoze Kimambo, Gerald (International journal of multilingualism, 2025)
The main argument of this paper is that the Virtual Linguistic Landscape (VLL) of advertising allows the utilisation of persuasion strategies that transcend the traditional separation of named languages to produce the maximum effect on potential customers. The paper challenges the segregational view of language, which assumes that communication involves selecting linguistic resources from pre-determined sets of possibilities in a separate linguistic system from other communicative possibilities (Pennycook, A. (2017). Translanguaging and semiotic assemblages. International Journal of Multilingualism, 14(3), 269-282, p. 8). It used the Snipping Tool to collect 79 online car adverts from X, Facebook, Instagram, Kupatana, Jiji Tanzania, and Jamii Forums. Thematic and socio-semiotic analyses indicate that advertisers for used cars integrate icons, indices, and symbols in the VLL to communicate messages effectively. They also utilise repetitions, typography, nonce borrowings, nicknames, colloquialisms, endorsements, and testimonials to influence their audiences' attitudes and behaviours. The paper also shows that communication in the VLL is shaped by the relations between users, semiotic possibilities, and referents in making meaning, lending support to translanguaging.